2005
DOI: 10.1002/biof.5520250116
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of statin adverse effects with supplemental Coenzyme Q10 and statin drug discontinuation

Abstract: Fifty consecutive new cardiology clinic patients who were on statin drug therapy (for an average of 28 months) on their initial visit were evaluated for possible adverse statin effects (myalgia, fatigue, dyspnea, memory loss, and peripheral neuropathy). All patients discontinued statin therapy due to side effects and began supplemental CoQ(10) at an average of 240 mg/day upon initial visit. Patients have been followed for an average of 22 months with 84% of the patients followed now for more than 12 months. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
8

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 8 publications
0
44
0
8
Order By: Relevance
“…Treatment with coenzyme Q10 reverses statin-induced fatigue and neurocognitive symptoms (Langsjoen et al 2005;Passi et al 2003). Curcumin and analogues inhibit ROS-induced lipid peroxidation and protein damage in mitochondria (Wei et al 2006).…”
Section: Mitochondria As New Drug Targets In Depressionmentioning
confidence: 99%
“…Treatment with coenzyme Q10 reverses statin-induced fatigue and neurocognitive symptoms (Langsjoen et al 2005;Passi et al 2003). Curcumin and analogues inhibit ROS-induced lipid peroxidation and protein damage in mitochondria (Wei et al 2006).…”
Section: Mitochondria As New Drug Targets In Depressionmentioning
confidence: 99%
“…CoQ10 supplementation (100 mg/d) for 30 d has been found to decrease the muscle pain associated with statin treatment [35] . In another study, fifty consecutive new patients discontinued 28 mo of statin therapy due to side effects and began CoQ10 supplementation at an average of 240 mg/d [36] and were followed for an average of 22 mo (84% for more than 12 mo). The prevalence of fatigue from 84% on the initial visit decreased to 16%, the rate of myalgia from 64% to 6%, dyspnea from 58% to 12%, memory loss from 8% to 4% and peripheral neuropathy from 10% to 2%.…”
Section: Of Mitochondria In the Cardiomyocytesmentioning
confidence: 99%
“…The prevalence of patient symptoms on initial visit and on most recent follow-up demonstrated a decrease in fatigue from 84% to 16%, myalgia from 64% to 6%, dyspnea from 58% to 12%, memory loss from 8% to 4% and peripheral neuropathy from 10% to 2%. They concluded that statin-related side effects, including statin cardiomyopathy, are far more common than previously published and are reversible with the combination of statin discontinuation and supplemental CoQ10, and they saw no adverse consequences from statin discontinuation [151]. Statin drugs (3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors) reduce the level of cholesterol by inhibiting the synthesis of mevalonate, an intermediary in the cholesterol biosynthetic pathway.…”
Section: Coenzyme Q10mentioning
confidence: 99%